Stenostomum leucops (Dugès 1828) (Platyhelminthes, Catenulida) reprodução, auxílio no esclarecimento filogenético e transformação genética. - Rosa, Marcos Trindade da (2017)
Stenostomum leucops is a platyhelminthe belonging to class Catenulida, presenting great morphological plasticity and preponderantly asexual reproduction, by paratomy. The time required for a complete formation of the zooids of approximately 42.5 hours at 28 ° C. A variety of energy production features and systems, making this organism an excellent candidate for model organism for regeneration studies, as a bioindicator or for others Studies involving asexual reproduction, such as a genetic transformation in somatic cells. In this study, in addition to estimating the rate and speed of asexual reproduction, the number of cells in the organism was quantified. The number of cells in the zooids, soon after a paratomy, is approximately 2,500. Employing DNA bar code added evidence the hypothesis that this rate corresponds to a complex of species. The first mitogenome of a Catenulide was described in the study and showed some of the related articles in other already noted planlmints. The genes are not mitogenic of S. leucops are encoded in both ribbons, while in other flatworms are encoded in only one strand. The gene order found in S. leucops is very divergent from observation in other flatworms. The atp8 gene is absent in other flatworms, but a highly divergent hypothetical atp8 gene has been found in S. leucops. Additionally, it is suggested that the anticodonate found not RNA transporter K (trnK) is a plesiomorphic condition that may explain how there is no genetic code of catenulide. An analysis of the regeneration pattern allowed us to observe four different regeneration routes related to the developmental stages of zoonoids. A genetic transformation is easily obtained in this species, with a fairly efficient expression transition, at least for the green fluorescent protein (GFP) reporter gene. GFP expression rapidly found shortly after 24 hours was observed when the lengths were electroporated with plasmids, as well as, although less effectively.